REVIEW ON FORMULATION AND EVALUATION OF ANTI-ACNE CONCEALER - Chaudhari, Rahul; Ajay, Dongarwar; Chaudhari, Rahul; Priti, Neware; Raut, Priyanka (International Journal of Pharma and Bio Sciences, 2026)
Acne is a chronic inflammatory skin disorder that involves the pilosebaceousgland. It is a common universal disease affecting about 85% of adolescents. Acne is a socially distressing skin condition created by propionibacterium acne, which has generally been treated with antibiotics. In the previous reported researches and review study, many types of concealer were prepared and used against acne and dermatitis to treat them. A concealer, a color corrector, is a cosmetic product that masks skin imperfections. These imperfections include dark circles under the eyes, blemishes, and hyperpigmentation. The formulation of medicated concealer, which includes dimethicone, Kojicdipalmitate, magnesium aluminum silicate, and propylene glycol, was carried out. The ingredients used in the preparation of cosmetics with their desirable properties to enhance the quality of the product in such a waythat they have the properties of good penetration, control release of medicament, maintain good compatibility of the active ingredients with other excipients, product stability in different conditions and provide better skin protection from sun rays. The concealer contains qualities like moisturizing, conditioning, emollient effects, anti-bacterial properties, etc., typically used to treat acne. This review includes types of acne, factors responsible, and common contents included in the concealer with their properties.